Does Moderate to Vigorous Physical Activity Fully Offset the Cardiometabolic Risks of Prolonged Sitting? A Review of Current Evidence - Anczyk, Antoni; Karolina Handzel,; Jacek Wysoczański,; Wiktoria Śliwa,; Wiktoria Tłoczek,; Daria Twardowska,; Dominik Kret,; Wiktoria Szlachta,; Krzysztof Karbowiak,; Natalia Nawrat,; Filip Basta, (Quality in Sport, 2026)
The aim of this paper is to discuss the “active couch potato” phenomenon, defined as a situation in which individuals who meet physical activity recommendations simultaneously spend a very large amount of time sitting, and to answer the question of whether regular exercise can fully compensate for the metabolic consequences of a sedentary lifestyle. Based on studies from recent years, the combined effects of sitting time, activity of varying intensity, metabolic profile status, adipose tissue (including visceral and hepatic fat), insulin resistance, risk of metabolic syndrome, and type 2 diabetes were analyzed. Data from population and interventional studies indicate that a high level of moderate-to-vigorous physical activity (MVPA) improves insulin sensitivity, lipid profile, and cardiovascular risk; however, prolonged, uninterrupted sitting remains an independent risk factor for poorer metabolic health, even in “sufficiently active” individuals [1, 5, 6, 8, 10, 19]. Individuals described as “active couch potatoes” – meeting activity recommendations but sitting >10 h/day – exhibit a less favorable cardiometabolic profile compared to individuals with a similar exercise volume but shorter sitting time and a greater proportion of light-intensity activity [6, 8, 19]. Short-term reductions in step count and increases in sitting lead to rapid deterioration of insulin receptor sensitivity, increased liver fat, and worsening dyslipidemia, partially reversible after returning to habitual movement levels [1, 5, 15]. Available data suggest that regular exercise markedly reduces, but does not completely eliminate, the adverse effects of prolonged sitting. Therefore, the optimal strategy includes a combination of MVPA, reduction of total sitting time, and frequent interruption of sitting with short episodes of light- or moderate-intensity activity.